Incorporation of Homochirality into a Zeolitic Imidazolate Framework Membrane for Efficient Chiral Separation - Chan, Jun Yong; Zhang, Huacheng; Nolvachai, Yada; Hu, Yaoxin; Zhu, Haijin; Forsyth, Maria; Gu, Qinfen; Hoke, David E.; Zhang, Xiwang; Marriot, Philip J.; Wang, Huanting (Angewandte Chemie International Edition, 2018)
Homochiral metal–organic frameworks (MOFs) have gained much attention because of their chiral properties and disposition for chiral separation. However, the fabrication of high‐quality homochiral MOF membranes remains challenging because of the difficulty in controlling growth of MOF membranes with chiral functionalities. A homochiral zeolitic imidazolate framework‐8 (ZIF‐8) membrane is reported for efficient chiral separation. The membrane is synthesized by incorporating a natural amino acid, l‐histidine (l‐His), into the framework of ZIF‐8. The homochiral l‐His‐ZIF‐8 membrane exhibits a good selectivity for the R‐enantiomer of 1‐phenylethanol over the S‐enantiomer, showing a high enantiomeric excess value up to 76 %. Handpicked: A homochiral zeolitic imidazolate framework‐8 (ZIF‐8) membrane was synthesized by incorporating a natural amino acid, l‐histidine (l‐His), into a ZIF framework. The amino acid functions as a chiral (enantiopure) ligand. The l‐His‐ZIF‐8 membrane demonstrates good homochirality and an ability to separate racemic 1‐phenylethanol with up to 76 % ee.